Knock-Out of CmNAC-NOR Affects Melon Climacteric Fruit Ripening - Liu, Bin; Santo Domingo, Miguel; Mayobre, Carlos; Martín-Hernández, Ana Montserrat; Pujol, Marta; Garcia-Mas, Jordi (Frontiers in Plant Science, 2022)
Fruit ripening is an important process that affects fruit quality. In melon, ETHQV6.3, a QTL involved in climacteric ripening regulation, was previously found to be encoded by CmNAC-NOR, a homologue of the tomato NOR gene. To further investigate CmNAC-NOR function we have obtained two CRISPR/Cas9 mediated mutants (nor-3 and nor-1) in the climacteric Védrantais background. nor-3, containing a 3-bp deletion altering the NAC domain A, resulted in ~8 days delay of ripening without affecting fruit quality. In contrast, nor-1 contained a 1-bp deletion resulting in a fully disrupted NAC domain, which completely blocked climacteric ripening. nor-1 fruits did not produce ethylene, abscission layer was not formed and there was no external color change. Additionally, volatile components were dramatically altered, seeds were not well developed and flesh firmness was also altered. nor-1 allele in heterozygosis showed ~20 days delay of fruit ripening. Our results provide new information regarding the function of CmNAC-NOR in melon fruit ripening, suggesting that it as a potential target to modulate shelf life in climacteric melon commercial varieties.